2014
DOI: 10.1371/journal.pone.0102540
|View full text |Cite|
|
Sign up to set email alerts
|

Lactate and the Lactate-to-Pyruvate Molar Ratio Cannot Be Used as Independent Biomarkers for Monitoring Brain Energetic Metabolism: A Microdialysis Study in Patients with Traumatic Brain Injuries

Abstract: BackgroundFor decades, lactate has been considered an excellent biomarker for oxygen limitation and therefore of organ ischemia. The aim of the present study was to evaluate the frequency of increased brain lactate levels and the LP ratio (LPR) in a cohort of patients with severe or moderate traumatic brain injury (TBI) subjected to brain microdialysis monitoring to analyze the agreement between these two biomarkers and to indicate brain energy metabolism dysfunction.MethodsForty-six patients with an admission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 52 publications
(95 reference statements)
1
36
0
Order By: Relevance
“…At 0.3 mL/min, we found a lower pyruvate limit of 39 mmol/L in anesthetized patients, corresponding to a true [Pyr] brain of $55 mmol/L. This value was similar to the lower limit obtained by Reinstrup et al 10 Our upper limit for the LP ratio was 34.2 at a perfusion rate of 0.3 mL/min, and it was 39.2 when using the ZFM data (Table 4); this corresponds to a LP ratio that is above [35][36][37][38][39][40], as suggested by the 2014 microdialysis consensus conference. 20 Therefore, the limit of 25 we suggested in a previous paper is likely too low to indicate ischemic or non-ischemic brain hypoxia or mitochondrial dysfunction.…”
Section: Thresholds For Pyruvate and The Lactate-pyruvate Ratiosupporting
confidence: 87%
See 1 more Smart Citation
“…At 0.3 mL/min, we found a lower pyruvate limit of 39 mmol/L in anesthetized patients, corresponding to a true [Pyr] brain of $55 mmol/L. This value was similar to the lower limit obtained by Reinstrup et al 10 Our upper limit for the LP ratio was 34.2 at a perfusion rate of 0.3 mL/min, and it was 39.2 when using the ZFM data (Table 4); this corresponds to a LP ratio that is above [35][36][37][38][39][40], as suggested by the 2014 microdialysis consensus conference. 20 Therefore, the limit of 25 we suggested in a previous paper is likely too low to indicate ischemic or non-ischemic brain hypoxia or mitochondrial dysfunction.…”
Section: Thresholds For Pyruvate and The Lactate-pyruvate Ratiosupporting
confidence: 87%
“…As we discussed in a previous paper, the best available estimate for upper brain lactate levels derives from studies of CSF and from a few studies of patients operated on in neurosurgical procedures in whom brain MD were monitored under general anesthesia and using different anesthetic management techniques. 36 These studies and others-conducted in severe TBI and patients with SAH-found that certain lactate thresholds were related to poor clinical outcomes, and the upper limit for brain lactate most widely used in neurocritical patients is extremely variable (range: 1.50 to 5.10). 11,13,16,17,37 The 2014 cerebral microdialysis consensus statement recommended 4 mmol/L as the upper reference limit.…”
Section: The Anaerobic Threshold Revisitedmentioning
confidence: 98%
“…Similarly, while TNF signaling is detrimental to CNS homeostasis, transforming growth factor-β (TGF-β) is strongly neuroprotective as signaling acts to reduce inflammation, excitotoxicity and apoptosis, and to enhance neuronal regeneration [for review, see (31)]. The trend toward increased lactate release in females is also intriguing, as lactate levels are increased during several types of brain injury and are thought to both indicate and enhance tissue damage (63,102). Thus, alcohol-induced astrocyte dysfunction in females is predicted to accelerate alcohol-induced neurotoxicity in a sexually dimorphic fashion.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 In addition, ''metabolic crisis,'' defined by a high lactate/pyruvate ratio (L/P), was associated with poor prognosis. 32,33 Metabolic crisis was further dichotomized based on brain lactate concentration ([Lac]b), rCBF, and PbtO 2 : type 1 (ischemic) displays high [Lac]b whereas type 2 (nonischemic) displays normal to low [Lac]b. 32,33 By contrast, ''aerobic hyperglycolysis,'' defined as high [Lac]b and low L/P with rCBF and PbtO 2 within physiological ranges, was associated with good prognosis.…”
Section: Introductionmentioning
confidence: 99%